Biological aspects of brown-marbled grouper (Epinephelus fuscoguttatus) from Taka Bonerate National Park, District of Selayar Islands, South Sulawesi, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fatma, Mallawa A, Najamuddin, Zainuddin M, Ayyub FR. 2022. Biological aspects of brown-marbled grouper (Epinephelus fuscoguttatus) from Taka Bonerate National Park, District of Selayar Islands, South Sulawesi, Indonesia. Biodiversitas 23: 1140-1153. Knowledge regarding biological aspects of fishes such as the brown-marbled grouper can provide important information for fisheries management. This research was conducted from February 2020 to February 2021 to determine the length-weight relationship, condition factor, gonad maturity stage and spawning pattern, size at first maturity and feeding habits of brown-marbled groupers in Taka Bonerate National Park. The sample caught comprised 1042 brown-marbled groupers with a total length (TL) range of 23-97 cm and a weight range of 0.5-17.6 kg. The length-weight equation was W: 0.0001?L2.5955 (R²: 0.8935). For male brown-marbled grouper (n: 569), TL range was 47-97 cm, weight range 1.65-17.60 kg, regression equation W: 0.0002?L2.4731 (R²: 0.7716), condition factor range 0.56-2.36 (mean 1.236±1.019), and length at first maturity 66.34 cm. For female brown-marbled grouper (n: 473) TL range was 23-73 cm (mean 46.84 cm), weight range 0.50-6.6 kg (mean 2.23 kg), regression equation W: 0.0007?L2.1057 (R²: 0.7416), condition factor range 0.55-2.17 (mean 1.225±1.018), and length at first maturity 45.43 cm. The growth pattern was negative allometric with regression coefficient b < 3 for both sexes separately and combined. The majority of both male and female fish caught had mature gonads with indications of a partial spawning pattern. The fish diet was carnivorous, predominantly piscivorous (74%), with gut contents comprising 64% unidentified fish and 26% unidentified decapod crustaceans. Over-exploitation of fish can cause negative impacts on populations, so the relationship between length and weight, condition factors and maturity level gonad of fish can be used in fisheries management.
Keywords: Condition factor, Epinephelus, feeding habit, length-weight